The Role of Al-Quran Literacy in Deepening Understanding of Islamic Religious Education - Siti Nurkholifah (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
This research focuses on the role of Al-Qur’an literacy in deepening students’ understanding of Islamic Religious Education and developing their moral and ethical character. This research explores how Al-Qur’an literacy functions as a reading skill and a tool for developing critical, reflective thinking and a holistic understanding of Islamic teachings. This research uses qualitative methods, including interviews, observation, and documentation techniques, to explore Al-Qur’an literacy experiences, perceptions, and practices at Middle School. The research results show that Al-Qur’an literacy significantly impacts understanding Islamic Religious Education material and developing students’ character. However, this research also identified challenges in implementation, such as a need for more time allocation in the curriculum and variations in reading skill levels among students. The implications of this research emphasize the need for adaptive learning strategies and additional support to increase the effectiveness of Al-Qur’an literacy in religious education.